HR ANALYTICS READINESS IN SMEs: BARRIERS, ENABLERS, AND STRATEGIC IMPACT - Supardi Supardi; Rizka Noor Miftakhul Ulum; Lisbet Situmorang (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to assess the readiness of Small and Medium Enterprises (SMEs) to adopt Human Resource (HR) Analytics, focusing on barriers, enablers, and the resulting strategic impact. Using a literature review method, this study examines various academic sources, industry reports, and practical publications to identify common patterns and key findings related to the implementation of HR Analytics in the SME sector. The study results indicate that the main barriers include limited technological resources, low data literacy, and resistance to organizational culture change. Conversely, enabling factors include visionary leadership, the availability of analytics training, and government policy support. The literature findings also indicate that effective implementation of HR Analytics can have strategic impacts in the form of improved data-driven decision-making, optimized employee performance, and strengthened long-term competitiveness. This study provides practical implications for SME owners and policymakers to develop more structured and sustainable HR Analytics readiness strategies.